Guía metodológica para el desarrollo de una auditoría de sistemas a un corresponsal bancario (2021)
Considering the rise of the network of banking correspondents in response to the current pandemic situation, with banks being an alternative to reducing their attention span in offices and for trader an extra income,the article below aims to propose a methodological system audit guide to banking correspondents in Colombia that contributes to provision of safe services, functional and transparent that generate trust to customers, correspondent, banks and control bodies. To carry out a system audit to a banking correspondent it is necessary to apply a methodology such as that provided by ISO 19011:2018 that provides the guidelines for its realization, in addition to carrying out field and documentary investigations that contribute to the know ledge of the contexts associated with the operation of a banking correspondent and the use of procedures, techniques and systems audit tools to develop the audit.